Perguraun Tinggi dalam Mempersiapkan Keterampilan Non-Teknis Mahasiswa di Era Revolusi Industri 4.0 - Mohammad Rodli (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Education in thisali era of digital disturbances cannot predict what will happen to future graduates who are preparing for new positions and professions that will emerge, driven not only by the fourth industrial revolution, but also by non-technological factors such as demographic pressure , geopolitical change, and social and cultural norms that occur through the discovery of new functions, and the mobility of people through reflecting new roles by digital technology is not an ordinary labor or ordinary capital ; but people who can create new ideas and innovations. The purpose of this paper is to describe the non-technical skills of Islamic religious teachers prepared in the era of industrial revolution 4.0. 1) Non-technical skills are known as the main attributes for graduates to be employed, for this reason the university is creating a sustainable pathway to develop leadership to create a vision that is in line with the needs of college stakeholders that include lectures that combine great opportunities and practices, such as practice-based final assignments that are integrated into lectures from the beginning of the program and new mentoring components were designed based on professional knowledge. 2) Non-technical skills that are capable of being accepted in the Industrial 4.0 era must at least contain Knowledge Work elements that have a role to mediate knowledge worker productivity between process management (knowledge generation, knowledge sharing, and knowledge applications) and innovation . 3) The second non-technical skill is Thinking Tools to develop optimal solutions to technical problems that depend on structured and complex thinking, technology design and programming, critical thinking and analysis and system analysis and evaluation capabilities. 4) The dynamic non-technical skills of a learning research consists of originality and creativity initiatives, ability to solve problem solving and reasoning, problem solving and ideas. 5) The fourth non-technical skill is Digital Lifestyle in Leadership and social influence.